Kecerdasan Emosional dan Kemampuan Berpikir Kritis: Studi Empiris pada Pembelajaran Ekonomi di SMA Negeri 1 Mesuji Raya - Ni Wayan Luh Nova Ratna Sari; Ikbal Barlian (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to investigate the effect of emotional intelligence on students' critical thinking skills in economics learning for class XI of SMA Negeri 1 Mesuji Raya. The research method used is quantitative with an ex-post facto approach. Data were collected through questionnaires to measure emotional intelligence and tests to assess critical thinking skills, then analyzed using simple linear regression. The results showed that emotional intelligence had a significant effect on critical thinking skills, as evidenced by F_count ≥ F_table (36.078 ≥ 4.13), so H₀ was rejected and Hα was accepted. The regression equation (Y = 0.0095 + 0.4532X) shows that every increase in one emotional intelligence score contributes to an increase in critical thinking skills by 0.4532. The coefficient of determination of 52.23% indicates that emotional intelligence has a significant effect on critical thinking, while the remaining 47.77% is influenced by other factors.